Hybrid annuity contracts for road projects in India. - Peri, Ravi ([Manila] Asian Development Bank, 2019)
The hybrid annuity model is a popular type of public private partnership that has been used in India for roads and is being attempted in other sectors. This paper examines whether hybrid annuity contracts provide value for money. It deconstructs and evaluates the costs of such contracts in India. It finds that the model in its current format does offer value for money and suggests ways of enhancing this.
Keywords: Public-Private Partnership -- India; Public-private sector cooperation -- India; Electronic books